Influence of gases on casting expansion processes during their hardening - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
It has been experimentally shown that directional solidification of water and bismuth in glass and quartz cylindrical forms does not result in expansion of the castings perpendicular to the solidification direction. Therefore, such forms are not destroyed. This is due to the unobstructed release of gases during directional solidification of water and bismuth. Gases have a great influence on the expansion processes of castings when they solidify.